From the Indigeneous to the Religious Practices: Islamic Construction of the Local Tradition in South Sulawesi, Indonesia - Mustaqim Pabbajah (UIN Sunan Kalijaga Yogyakarta, 2021)
Islam and indigenous tradition in Indonesia have long established interconnected relations in both social and ritual practices. This study elaborates on the Islamic construction of the indigenous Bugis-Makassar tradition. The “Haji Bawakaraeng” is one the familiar practice and is believed to exist in the South Sulawesi region. Term Haji Bawakaraeng is a religious practice contained with local Muslim beliefs carried out on Mount Bawakaraeng. This research uses a descriptive qualitative approach with data collection done through observation, interviews, and documentation studies. This study finds that the Bugis-Makassar habit of carrying out a series of rituals on the summit of Mount Bawakaraeng is an old belief facing the process of negotiation and adaptation to the teachings of Islam. The presence of the term Hajj as an Islamic construction and Bawakaraeng as a local cultural construction is the result of the construction of Islam on the local beliefs of the Buginese-Makassarnese. In addition, this study also illustrates the dynamics of the inclusion of Islam in South Sulawesi as a variative and authentic inclusion. Finally, this study explains the diversity of the Bugis-Makassar people which tends to change from indigenous traditions to religious practices due to the ongoing construction of Islam. This paper recommends the need for further studies on the issue of religious and cultural relations at the micro level to see the dynamics of changing socio-religious practices in the community.